Urinary cell cycle arrest proteins urinary tissue inhibitor of metalloprotease 2 and insulin-like growth factor binding protein 7 predict acute kidney injury after severe trauma: A prospective observational study. Issue 4 (October 2020) - Hatton, Gabrielle E.; Wang, Yao Wei; Isbell, Kayla D.; Finkel, Kevin W.; Kao, Lillian S.; Wade, Charles E.
Abstract : BACKGROUND: Recognition and clinical diagnosis of acute kidney injury (AKI) after trauma is difficult. The majority of trauma patients do not have a known true baseline creatinine, which makes application of the guidelines set forth by the international guidelines difficult to apply. Use of alternative biomarkers of renal dysfunction in trauma patients may be beneficial. We hypothesized that urinary tissue inhibitor of metalloprotease 2 (TIMP-2) × insulin-like growth factor binding protein 7 (IGFBP-7) would accurately predict AKI development in severely injured trauma patients. METHODS: A prospective observational study of adult (≥16 years old) trauma intensive care unit (ICU) patients was performed between September 2018 to March 2019. Urine was collected on ICU admission and was measured for TIMP-2 × IGFBP-7. Univariate, multivariable, and receiver operating characteristic curve analyses were performed using the optimal threshold generated by a Youden index. MAIN RESULTS: Of 88 included patients, 75% were male, with a median injury severity score was 27 (interquartile range [IQR], 17–34), and age of 40 years (IQR, 28–54 years). Early AKI developed in 39 patients (44%), and of those, 7 (8%) required dialysis within 48 hours. Patients without early AKI had a TIMP-2 × IGFBP-7 of 0.17 U (IQR, 0.1–0.3 U), while patients with early AKI had a TIMP-2 × IGFBP-7 of 0.46 U (IQR, 0.17–1.29 U; p < 0.001). On multivariable analyses, TIMP-2 × IGFBP-7 was associated with AKI development ( p = 0.02) and need for dialysis ( p = 0.03). Using the optimal threshold 0.33 U to predict AKI, the area under the receiver operating characteristic curve was 0.731, with an accuracy of 0.75, sensitivity of 0.72, and specificity of 0.78. CONCLUSION: Urinary TIMP-2 × IGFBP-7 measured on ICU admission accurately predicted 48-hour AKI and was independently associated with AKI and dialysis requirement after trauma and is a promising screening tool for treatment. LEVEL OF EVIDENCE: Prognostic, prospective, observational study, level III. Abstract : Supplemental digital content is available in the text.